2020
DOI: 10.3389/fped.2020.00363
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Thromboembolic Pulmonary Hypertension in a Child With Sickle Cell Disease

Abstract: Chronic thromboembolic pulmonary hypertension is a potentially curable form of pre-capillary pulmonary hypertension (PH) resulting from incomplete resolution of pulmonary thromboemboli. We describe an 11-year-old boy with homozygous sickle cell disease with an indwelling catheter found to have severe PH on routine screening echocardiography. The diagnosis was confirmed by CT, ventilation-perfusion scintigraphy, and right heart catheterization. The patient was medically managed until undergoing pulmonary thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Lambert et al described the first case of CTEPH in an infant related to a Broviac-catheter in 1999, who underwent PTE after a failed attempt of systemic thrombolytic therapy ( 23 ). Spencer et al presented a case of CTEPH in an 11-year-old boy with sickle cell disease and a history of CVC-related thrombosis, who was primarily unsuccessfully treated with anticoagulant therapy and PTE was therefore performed in the later clinical course ( 4 ). Humpl et al reported on a case of PTE after ineffective anticoagulation in a 16-month-old girl suffering from CTEPH associated with a peritoneovenous Denver shunt ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lambert et al described the first case of CTEPH in an infant related to a Broviac-catheter in 1999, who underwent PTE after a failed attempt of systemic thrombolytic therapy ( 23 ). Spencer et al presented a case of CTEPH in an 11-year-old boy with sickle cell disease and a history of CVC-related thrombosis, who was primarily unsuccessfully treated with anticoagulant therapy and PTE was therefore performed in the later clinical course ( 4 ). Humpl et al reported on a case of PTE after ineffective anticoagulation in a 16-month-old girl suffering from CTEPH associated with a peritoneovenous Denver shunt ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pulmonary thromboendarterectomy (PTE) is the treatment of choice in adult patients ( 10 ). Whereas PTE is associated with excellent short and mid-term results (1-year survival 93% and 3-year survival 89%) in the adult population ( 11 ), data for pediatric CTEPH patients is deemed insufficient as they roughly present 1% of all CTEPH cases ( 4 , 5 , 12 , 13 ). Herein, we present two pediatric patients who received a Hickman-catheter for parenteral nutrition and developed CVC-related thrombosis complicated by PE.…”
Section: Introductionmentioning
confidence: 99%
“…The North American guidelines for pediatric cardiac catherization defined as significant stenosis when there is relative flow discrepancy between the 2 lungs of 35%/65% or worse ( 83 ). LPS also is one of the imaging techniques that can be used for etiological assessment of pulmonary arterial hypertension (PAH) in children ( 84 , 85 ). In pulmonary vein stenosis, the LPS sensitivity is 72% and specificity is 83% for all veins when compared with the angiographic findings ( 86 ).…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The findings of the above study can be compared in parallel to another study that was performed in 2013, where it was found that people with TRV >2.5 m/s and variant subtypes had an elevated risk of developing thromboembolic events [ 37 ]. Some of the risk factors that increase the risk of pulmonary thromboembolism are mentioned in Table 2 [ 38 ].…”
Section: Reviewmentioning
confidence: 99%
“…As stated above, the group four category of the classification of pulmonary hypertension encompasses the etiologies that are caused by pulmonary thromboembolism. An interesting case report that was published in 2020 highlighted the presence of pulmonary hypertension due to thromboembolism in an 11-year-old child with a homozygous trait for SCD [ 38 ]. The use of parameters like D-dimers in patients with SCD for screening thromboembolism lacks reliability as the baseline D-dimer levels vary by a huge margin [ 39 ].…”
Section: Reviewmentioning
confidence: 99%